The Relationship between Stress and Eating Behavior in Final Year Students Working on a Thesis at HKBP Nommensen University - Hernika Lumbantoruan; Siahaan, Ervina Marimbun Rosmaida (Jurnal Ilmiah Sumber Daya Manusia, 2024)
This research aims to examine the relationship between stress and eating behavior among final-year students working on their theses at HKBP Nommensen University in Medan. The study employs a quantitative research method, with a sample of 145 final-year students who are currently completing their theses at HKBP Nommensen University. Based on the Pearson Product Moment correlation test, the results show a significant relationship, with a p-value of 0.000 (p<0.05). The study also reveals a negative correlation between stress and eating behavior, with r = -0.747. This indicates that as stress levels increase, eating behavior decreases, and conversely, as stress levels decrease, eating behavior increases.